Analisis Yuridis Terhadap Penerapan Hukum Adat Karo Tentang Perkawinan Semarga - Rayani Saragih; Gio Fani Sembiring; Gabriel Nickodemus Ginting (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Customary law is something that is very inherent in Indonesian society, because it is still growing and being applied in the midst of society to this day. Among the many customs that exist in Indonesia, the Karo custom is one that is still very heavily applied. Adat Karo has provisions related to the customary culture of its indigenous people, both related to marriage, inheritance distribution, and other customary practices in accordance with the activities carried out. This research method is juridical and normative analysis, data sources are carried out in literature and in the field. Field research conducted interviews in Gongsol Village, Karo District. The purpose of this writing is to find out and analyze the rules for the application of Karo customary law regarding same-sex marriage. The results of this study are that the marriage rules in the Karo custom are in the form of an agreement between the two parties, namely the introduction of the parents of both parties, ngembah belo a sheet, ngantik manuk, ngalari customary debt (party), hitting after the Karo traditional party is finished. In traditional Karo marriages, it is not permissible to marry with the same clan, this has become customary law in Karo customs, and if this happens, they will be expelled from the local village/village.